Research progress of prevention and nursing interventions for mechanical phlebitis after peripherally inserted central catheter placement (PICC置管后机械性静脉炎预防与护理进展) - LIU Jinjing (刘津京) (Association of Integrative Nursing, 2021)
Given the widespread use of peripherally inserted central catheter (PICC)in clinical settings, it is required to enhance the prevention and treatment on catheter-related complications. This paper reviewed the studies about prevention and nursing interventions for mechanical phlebitis after PICC placement, including catheterization process, application of hydrocolloid dressings, external application of drugs, physiotherapy and Traditional Chinese Medicine techniques. (经外周静脉置入中心静脉导管(PICC)在临床中广泛应用, 相关并发症的防治至关重要。本文综述了PICC置管后机械性静脉炎预防与护理进展, 包括置管操作、水胶体敷料的应用、药物外敷、物理治疗、中医适宜技术等。)